Antagonistic specificity of isolates of trichoderma SPP. against isolates of rhizoctonia solani from cotton roots - Osman, Eman A. M.; Omar, M. R.; El-Samawaty, A. M.; Eisa, H. A. (2009)
Biocontrol efficiency of four isolates of T, harzianum and T. viride werw evaluated against twelve isolates of Rhizoctonia solani under greenhouse.
Includes reference.
Summary in Arabic.
1
Keywords: Cotton -- Seedlings; Cotton -- Diseases and pests -- Biological control; Trichoderma; Rhizoctonia; Phytopathogenic microorganisms -- Biological control